Critical points regarding the use of mediation in companies (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Disputes in workplaces are very common, so mediation could be a useful and appropriate choice to solve them. However, we find that mediation is used in an irregular way in labor context. In collective relationships, mediation is quite extended considering the character of the disputes and Collective Agreement regulation. But in individual work relationship, there are some obstacles that have commonly been argued regarding mediation and it’s necessary a higher public support.
Keywords: Mediation; work relationship; private dispute resolutions.